An evaluation of the cost of human papilloma virus (HPV) vaccine delivery in Zambia - Simuyemba, Moses C.; Sinyangwe, Aaron; Asiimwe, Gilbert; Masiye (BMC Infectious Diseases, 2024)
Human papillomavirus (HPV) is a common sexually transmitted infection and the leading cause of cervical cancer. The HPV vaccine is a safe and effective way to prevent HPV infection. In Zambia, the vaccine is given during Child Health Week to girls aged 14 years who are in and out of school in two doses over two years. The focus of this evaluation was to establish the cost to administer a single dose of the vaccine as well as for full immunisation of two doses. This work was part of a broader study on assessing HPV programme implementation in Zambia. For HPV costing aspect of the study, with a healthcare provider perspective and reference year of 2020, both top-down and micro-costing approaches were used for financial costing, depending on the cost data source, and economic costs were gathered as secondary data from Expanded Programme for Immunisation Costing and Financing Project (EPIC), except human resource costs which were gathered as primary data using existing Ministry of Health salary scales and reported time spent by different health cadres on activities related to HPV vaccination. Data was collected from eight districts in four provinces, mainly using a structured questionnaire, document reviews and key informant interviews with staff at national, provincial, district and health facility levels. Administrative coverage rates were obtained for each district. Findings show that schools made up 53.3% of vaccination sites, community outreach sites 30.9% and finally health facilities 15.8%. In terms of coverage for 2020, for the eight districts sampled, schools had the highest coverage at 96.0%. Community outreach sites were at 6.0% of the coverage and health facilities accounted for only 1.0% of the coverage. School based delivery had the lowest economic cost at USD13.2 per dose and USD 28.1 per fully immunised child (FIC). Overall financial costs for school based delivery were US$6.0 per dose and US$12.4 per FIC. Overall economic costs taking all delivery models into account were US$23.0 per dose and US$47.6 per FIC. The main financial cost drivers were microplanning, supplies, service delivery/outreach and vaccine co-financing; while the main economic cost drivers were human resources, building overhead and vehicles. Nurses, environmental health technicians and community-based volunteers spent the most time on HPV related vaccination activities compared to other cadres and represented the greatest human resource costs. The financial cost of HPV vaccination in Zambia aligns favourably with similar studies conducted in other countries. However, the economic costs appear significantly higher than those observed in most international studies. This discrepancy underscores the substantial strain placed on healthcare resources by the program, a burden that often remains obscured. While the vaccine costs are currently subsidized through the generous support of Gavi, the Vaccine Alliance, it’s crucial to recognize that these expenses pose a considerable threat to long-term sustainability. Consequently, countries such as Zambia must proactively devise strategies to address this challenge.